A comparison of the acceptability and psychometric properties of scales assessing the impact of type 1 diabetes on quality of life—Results of 'YourSAY: Quality of Life'. Issue 6 (5th February 2021) - Holmes‐Truscott, Elizabeth; Cooke, Debbie D.; Hendrieckx, Christel; Coates, Elizabeth J.; Heller, Simon R.; Speight, Jane
Abstract: Aims: To compare the acceptability, reliability and validity of five contemporary diabetes‐specific quality of life (QoL) scales among adults with type 1 diabetes in the United Kingdom and Australia. Methods: Adults with type 1 diabetes (UK = 1139, Australia = 439) completed a cross‐sectional, online survey including ADDQoL‐19, DCP, DIDP, DSQOLS and Diabetes QoL‐Q, presented in randomised order. After completing each scale, participants rated it for clarity, relevance, ease of completion, length and comprehensiveness. We examined scale acceptability (scale completion and user ratings), response patterns, structure (exploratory and confirmatory factor analyses) and validity (convergent, concurrent, divergent and known groups). To assess cross‐country reproducibility, analyses conducted on the UK dataset were replicated in the Australian dataset. Results: Findings were largely consistent between countries. All scales were acceptable to participants: ≥90% completing all items, and ≥80% positive user ratings, except for DSQOLS' length. Scale structure was not supported for the DCP. Overall, in terms of acceptability and psychometric evaluation, the DIDP was the strongest performing scale while the ADDQoL‐19 and Diabetes QoL‐Q scales also performed well. Conclusions: These findings suggest that the recently developed brief (7 items), neutrally worded DIDP scale is acceptable to adults with type 1 diabetes and has the strongest psychometric performance. However, questionnaire selection should always be considered in the context of the research aims, study design and population, as well as the wider published evidence regarding both the development and responsiveness of the scales.